Violencia psicológica y su incidencia en las relaciones interpersonales de una mujer de 25 años de la ciudad de Babahoyo - Carpio Armache, Dexy Camila (2023)
This case study tells us how interpersonal relationships are affected by psychological violence to a 25-year-old woman from the city of Babahoyo, since psychological violence is a type of violence which significantly affects the state emotional state of a person, in this case that of the patient, who had been going through problems since she suffered psychological violence from her current partner and her interpersonal relationships, both family, social and work, were severely affected, therefore she was preceded by perform the respective interview and the psychometric tests to measure his level of depression since he had been presenting sadness, thoughts of insecurity and uselessness among them is the (BDI) Beck Depression Inventory and Depression Anxiety and Stress Scale (DASS-21) , in order to find a diagnosis, then proceeded to develop the psychotherapeutic scheme to carry out the respective therapies to deal with the problem. emmatic, improve the patient's mood and help her to continue with her life normally.